2007
DOI: 10.1097/psy.0b013e318148c682
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms Predict Mucosal Wound Healing

Abstract: Depressive symptoms predict the rate of mucosal wound healing in healthy young adults. We discuss potential pathways that warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 81 publications
1
57
0
1
Order By: Relevance
“…Depressed individuals also show patterns of immune alteration similar to those observed in chronic stress; e.g., impairments in some cellular immune parameters, delayed healing of experimentally administered wounds, and blunted antibody responses to vaccination, accompanied by increased systemic inflammatory activity (e.g., Bosch et al 2007;Glaser et al 2003;Irwin et al 1998;Kop et al 2002;Lesperance et al 2004;Miller et al 2002b; see reviews by Irwin 2001Irwin , 2002Raison et al 2006). Similar patterns are seen in both clinically depressed patients and those with high levels of dysphoric affect.…”
Section: Depressionmentioning
confidence: 55%
“…Depressed individuals also show patterns of immune alteration similar to those observed in chronic stress; e.g., impairments in some cellular immune parameters, delayed healing of experimentally administered wounds, and blunted antibody responses to vaccination, accompanied by increased systemic inflammatory activity (e.g., Bosch et al 2007;Glaser et al 2003;Irwin et al 1998;Kop et al 2002;Lesperance et al 2004;Miller et al 2002b; see reviews by Irwin 2001Irwin , 2002Raison et al 2006). Similar patterns are seen in both clinically depressed patients and those with high levels of dysphoric affect.…”
Section: Depressionmentioning
confidence: 55%
“…Psychological stress and elevated cortisol levels can have an impact on wound repair (Christian, Grahamf, Padgetta, Glasera & Kiecolt-Glaser, 2006;Gouin & Kiecolt-Glaser, 2011), this has been confirmed also regarding mucosal wounds (Bosch, Engeland, Cacioppo & Marucha, 2007). The mechanism might be linked to proinflammatory cytokines, which play an important role in the wound healing process, protecting the wound site from infection and preparing the wound for repair (Glaser, 2005).…”
Section: Physiological Pathways Of Cortisol and Its Possible Influencmentioning
confidence: 81%
“…In contrast, comparison between the experimental punch biopsy wound studies [49,50,63,64,67,68] was facilitated by the fact that the wounds in these studies were of a standard size with reduced measurement variability. Indeed, most punch biopsy studies demonstrated the reliability and validity of their measurements.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of stressors were measured, the most popular (10 studies) being brief naturalistic stressors (i.e., surgical procedures and academic examinations) followed by global stress appraisals [43,45,50,63,67]. Less common were acute time limited stressors [22, 48,59], chronic stressors [64,65], stressful event sequences (i.e., marital difficulties) [48,62], and distant stressors [60].…”
Section: J Walburn Et Al / Journal Of Psychosomatic Research XX (20mentioning
confidence: 99%